Prognostic significance of programmed cell death ligand 1 blood markers in non-small cell lung cancer treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Zhang, Ningning; Chang, Jianlan; Liu, Ping; Tian, Xiangyang; Yu, Junyan (Frontiers in Immunology, 2024)
Background: Immune checkpoint inhibitors (ICIs) are effective for non-small cell lung cancer (NSCLC) treatment, but the response rate remains low. Programmed cell death ligand 1 (PD-L1) in peripheral blood, including soluble form (sPD-L1), expression on circulating tumor cells (CTCs PD-L1) and exosomes (exoPD-L1), are minimally invasive and promising markers for patient selection and management, but their prognostic significance remains inconclusive. Here, we performed a meta-analysis for the prognostic value of PD-L1 blood markers in NSCLC patients treated with ICIs.Methods: Eligible studies were obtained by searching PubMed, EMBAS, Web of Science, and Cochrane Library prior to November 30, 2023. The associations between pre-treatment, post-treatment and dynamic changes of blood PD-L1 levels and progression-free survival (PFS)/over survival (OS) were analyzed by estimating hazard ratio (HR) and 95% confidence interval (CI).Results: A total of 26 studies comprising 1606 patients were included. High pre/posttreatment pre-or post-treatment sPD-L1 levels were significantly associated with worse PFS (pre-treatment: HR=1.49, 95%CI 1.13-1.95; post-treatment: HR=2.09, 95%CI 1.40-3.12) and OS (pre-treatment: HR=1.83, 95%CI 1.25-2.67; post-treatment: HR=2.60, 95%CI 1.09-6.20, P=0.032). High pre-treatment exoPD-L1 levels predicted a worse PFS (HR=4.24, 95%CI 2.82-6.38, P<0.001). Pre-treatment PD-L1 + CTCs tended to be correlated with prolonged PFS (HR=0.63, 95%CI 0.39-1.02) and OS (HR=0.58, 95%CI 0.36-0.93). Patients with up-regulated exoPD-L1 levels, but not sPD-L1, after ICIs treatment had significantly favorable PFS (HR=0.36, 95%CI 0.23-0.55) and OS (HR=0.24, 95%CI 0.08-0.68).PD-L1 blood markers, including sPD-L1, CTCs PD-L1 and exoPD-L1, can effectively predict prognosis, and may be potentially utilized for patient selection and treatment management for NSCLC patients receiving ICIs.